Rubber concrete reinforced with macro fibers recycled from waste GFRP composites: Mechanical properties and environmental impact analysis - Li, Shu-Jing; Huang, Shi-Qi; Kuang, You-Di; Zou, Qi-Qi; Wang, Lian-Kun; Fu, Bing (Case Studies in Construction Materials, 2024)
With the rapid growth of the automotive industry, a huge amount of tires have been produced, which inevitably led to the accumulation of scrap tires. A typical disposal routine is using scrap tires as a partial substitute for fine aggregate in concrete, producing so-called rubber concrete. However, the detrimental effects of rubber particles on concrete properties have been identified, which, to some content, hinders their broader application. The discrete fiber addition is shown to be effective in minimizing this detrimental effect, and this paper has therefore attempted to introduce macro fiber produced from waste glass fiber reinforced polymer (GFRP) into the rubber concrete system. Three series of specimens for compression, splitting, and flexural testing were tested. The test variables include concrete type (i.e., normal concrete, rubber concrete, and modified rubber concrete); and macro fiber content (i.e., 0–2 %). In addition, the inverse analysis is performed to transform the flexural test response into the tensile constitutive law of the fiber-reinforced concrete (FRC). The test results revealed macro fibers have little effect on the compressive strength of normal concrete and rubber concrete and a detrimental effect on that of modified rubber concrete. Incorporated fibers notably improve the splitting and flexural performance of normal concrete and rubber concrete. In addition, the cost and environmental impact analysis revealed that the addition of recycling products increases the concrete cost and results in a maximum reduction of carbon emissions by 17.3 % and embodied energy emissions by 80 %.